1978
DOI: 10.1252/jcej.11.276
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of absorption of sulfur dioxide and nitric oxide in aqueous mixed solutions of sodium chlorite and sodium hydroxide.

Abstract: The rates of single and simultaneous absorptions of dilute SO2 and NOin aqueous mixed solutions of NaClO2and NaOHwere measured at 25°C using a stirred vessel with a plain gas-liquid interface. In the SO2-NaClO2system, the absorption rate exceeded the gas-film controlled rate, which implies the possibility of gas-phase oxidation of SO2 due to the evolved C1O2. In the SO2-(NaClO2+NaOH) system, the absorption rate agreed with that under gas-film controlled conditions. In the (SO2+NO)-(NaClO2+NaOH)system, the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 2 publications
3
27
0
Order By: Relevance
“…5, where the slope is found to be 1.5, and the reaction order is determined to be m = 2. A similar observation was reported for NaClO 2 /NaOH solutions by Brogren et al [16], Chu et al [17], and Sada et al [23,26]. The average rate constant is 5.76 · 10 7 (m 3 /mol) 2 /s in the case of C Na 2 CO 3 20 mol m -3 .…”
Section: Effect Of Gas-liquid Interfacial No Concentration On No Absosupporting
confidence: 84%
See 1 more Smart Citation
“…5, where the slope is found to be 1.5, and the reaction order is determined to be m = 2. A similar observation was reported for NaClO 2 /NaOH solutions by Brogren et al [16], Chu et al [17], and Sada et al [23,26]. The average rate constant is 5.76 · 10 7 (m 3 /mol) 2 /s in the case of C Na 2 CO 3 20 mol m -3 .…”
Section: Effect Of Gas-liquid Interfacial No Concentration On No Absosupporting
confidence: 84%
“…4 that the NO absorption rate increases with increasing NaClO 2 concentration. The absorption rate of NO by NaClO 2 is regarded as being the m-th order relative to NO [6,16,20,23,26], which was expressed by Danckwerts [27] as given by Eq. (8):…”
Section: Effect Of Naclo 2 Concentration On Nomentioning
confidence: 99%
“…The diffusivity in an alkaline sodium chlorite solution can be calculated from the corresponding values of nitrous oxide [23] :…”
Section: Modeling the Absorptionmentioning
confidence: 99%
“…The diffusivity of N 2 O in the mixed salt solutions has been measured in a laminar liquid jet apparatus by Sada et al [23] .…”
Section: Modeling the Absorptionmentioning
confidence: 99%
“…This is mainly because of the formation of ClO 2 from the decomposition of NaClO 2 solution in acidic condition [11]. Moreover, ClO 2 − has stronger oxidability in acid condition, hence, the removal efficiency of Hg 0 is raised effectively [12,13]. The oxidation-reduction potential of ClO 2 − / Cl − was lower than that of Hg 2+ /Hg 0 (0.85 V) under alkaline condition, which indicated that Hg 0 could not be oxidized by alkaline NaClO 2 solution, as shown in Figure 3.…”
Section: Figurementioning
confidence: 99%